Space Race 2. 0 SpaceX, Blue Origin, Virgin Galactic, NASA, and the Privatization of the Final Frontier. - Bergan, Brad (Quarto Publishing Group USA, 2022)
With authoritative text and stunning photography, Space Race 2.0 traces the history of commercial space exploration from its tentative first steps in the 1990s to the incredible achievements of today and beyond.
Description based upon print version of record.
Keywords: Space industrialization -- United States.; Space race.; Entrepreneurship.; Outer space -- Exploration -- United States.; Conquête de l'espace.; Entrepreneuriat.; Espace extra-atmosphérique -- Exploration -- États-Unis.; entrepreneurs.; Entrepreneurship; Exploration of outer space; Space industrialization; Space race; Outer space; United States